TyG index and MAFLD severity are associated with subclinical LV dysfunction in T2DM patients: a cross−sectional study - Hu, Xiangsui; Chen, Hanwei; Wang, Ziying; Deng, Yun; Huang, Long; Zhang, Chunquan; Guo, Liangyun; Liu, Shengbo; Liao, Lingmin (Frontiers in Endocrinology, 2026)
BackgroundMetabolic dysfunction-associated fatty liver disease (MAFLD) is highly prevalent in type 2 diabetes mellitus (T2DM) and may contribute to early myocardial dysfunction. The Fibrosis-4 (Fib-4) index is a reliable marker of hepatic fibrosis, and the triglyceride-glucose (TyG) index is an effective indicator of insulin resistance (IR). Both are linked to various cardiovascular diseases (CVDs).However, their combined impact on subclinical left ventricular dysfunction (SLVD) remains unclear. This study aimed to explore the associations between hepatic fibrosis, IR, and SLVD in T2DM patients.MethodsWe enrolled 270 T2DM patients between September 2024 and April 2025.MAFLD was diagnosed by ultrasonography, hepatic fibrosis was assessed using the Fib-4 index, and insulin resistance was estimated using the TyG index formula. Left Ventricular Global Longitudinal Strain (LV GLS) was measured by speckle-tracking echocardiography, with SLVD defined as absolute value of LV GLS <18%. T2DM patients were divided into three groups based on the presence of MAFLD and Fib-4 <1.3 or ≥1.3: non-MAFLD, MAFLD+Fib-4<1.3, and MAFLD+Fib-4≥1.3, and further stratified by the TyG median. Multivariable logistic regression models were used to evaluate the independent and interactive associations of Fib-4 index and TyG index with SLVD.ResultsCompared to non-MAFLD patients, T2DM patients with MAFLD were younger, had a shorter duration of diabetes, and exhibited worsened lipid profile, with higher TyG values and lower LV GLS. MAFLD independently predicted SLVD (adjusted OR = 3.21, 95% CI: 1.64–6.29). Even in patients with Fib-4 <1.3, MAFLD was associated with higher SLVD risk (OR = 2.94), while advanced fibrosis further increased SLVD risk (OR = 3.68). TyG independently predicted SLVD (adjusted OR = 2.73, 95% CI: 1.48–5.03). Importantly, patients with both high Fib-4 (≥1.3) and high TyG (≥9.03) had the greatest SLVD risk (OR = 7.58), whereas advanced fibrosis alone was not significant.ConclusionsFib-4 index and TyG index are independent predictors of SLVD in T2DM, and their coexistence exerts a synergistic effect. Combined assessment provides a simple, non-invasive tool for early risk stratification, highlighting the clinical importance of the liver–heart axis in identifying SLVD.